Why Liquidity Matters to the Export Decision of the Firm - Chan, Rosanna (World Bank, Washington, DC, 2014)
Under financial constraints, exporting may have less to do with productivity and more to do with financial resources. The established relationship between exporting and productivity would differ when examined through the lens of the working capital needs of the firm. The hypothesis that working capital matters in the firm's exporting decision is explored in two ways: first, by articulating a dynamic working capital model of the firm that incorporates the firm's export decision. Secondly, by testing the hypothesis empirically using a unique firm level dataset from Bangladesh, where issues of financial constraints are particularly acute. The model shows that productivity determines export status of the firm as long as it is not under financial constraints. However, under financial constraints, export status is less dependent on productivity and more dependent on the availability of working capital. Empirical results support the model's prediction. The relationship between exporting time and the need for greater liquidity is also borne out empirically as shown by a positive and significant correlation between the amount of working capital and the distance of export destination. An important policy implication from the analysis is that short term liquidity is critical in allowing productive firms to export and that access to finance may prevent the benefits of trade liberalization within a country to be fully realized.